Enhancing Young Learners' Vocabulary through Interactive Learning Platform: Quizizz - Fikri Fuadi Azmy; Pajrian Noor; Halimah Apriliani (Universitas Muhammadiyah Tapanuli Selatan, 2026)
This research highlights the importance of learning English from an early age as a response to the challenges of globalization. English is key to accessing technology and global knowledge, emphasizing the need for students to master it from an early age. Vocabulary plays a crucial role in speaking, reading, writing and listening skills in English. Limited vocabulary can hinder comprehensive abilities in the language. This research uses the Classroom Action Research (CAR) classroom action method to investigate the effects of the Quizizz game in increasing English vocabulary in elementary schools. In two cycles, there was a significant increase from pre-test 60% to 94% after the first cycle, with the majority of students reaching or exceeding the school's KKM (70%). Quizizz is proven to be effective in increasing student interest and engagement with its competitive features and attractive design. This tool creates a fun learning environment and reduces boredom in learning. Students get immediate feedback and can track their progress, while teachers can monitor learning progress efficiently. The implications of this research suggest the use of interactive learning platform such as Quizizz in teaching English vocabulary in elementary schools. This can increase learning effectiveness and strengthen student motivation. This research also contributes to the understanding of game-based learning methods in the context of language education. Overall, this research provides practical guidance for teachers to integrate technology in English vocabulary learning in elementary schools, as well as providing a basis for further research in the development of game-based learning.